Teaching Style on Learning Outcomes of Dribbling the Ball in Extracurricular Futsal Games in High School - Mappaompo, M. Adam; Vaisal, Vaisal; Usman, Arifuddin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study differs from field results that many students still struggle with dribbling despite regular PJOK participation. Teachers' incorrect teaching approaches and student learning motivation may contribute to this situation. This study examines how instructional approaches affect futsal dribbling skills and learning motivation in High School 1 Sinjai Utara pupils. This study used a pure experimental method (true experimental design) with a 2x2 factorial design, involving 40 students who were randomly divided into two treatment groups, namely learning with a reciprocal teaching style and a practice teaching style. The research instruments included a futsal dribbling skills test and a learning motivation questionnaire to identify student characteristics. The research procedure was carried out through the pre-test, learning treatment, and post-test stages. The analysis found that (1) there was a significant difference in dribbling skill learning outcomes between the reciprocal teaching style and the practice teaching style; (2) learning motivation significantly influenced learning outcomes; (3) there was an interaction between teaching style and learning motivation; and (4) students with high learning motivation performed better. Thus, a reciprocal teaching style can be an effective futsal learning strategy, especially for students with high learning motivation, because it encourages active participation, mutual feedback, and continuous observation and correction to improve technical skills. This study suggests that PJOK teachers should tailor their teaching techniques to students' traits and motivations for more successful, student-centered skills learning.